Small-scale entrainment in inclined gravity currents - Van,Reeuwijk M; Krug,D; Holzner,M (Environmental Fluid Mechanics, 2017)
We investigate the effect of buoyancy on the small-scale aspects ofturbulent entrainment by performing direct numerical simulation of a gravity cur-rent and a wall jet. In both flows, we detect the turbulent/nonturbulent interfaceseparating turbulent from irrotational ambient flow regions using a range of en-strophy iso-levels spanning many orders of magnitude. Conform to expectation,the relative enstrophy isosurface velocityvnin the viscous superlayer scales withthe Kolmogorov velocity for both flow cases. We connect the integral entrainmentcoefficientEto the small-scale entrainment and observe excellent agreement be-tween the two estimates throughout the viscous superlayer.The contribution ofbaroclinic torque tovnis negligible, and we show that the primary reason forreduced entrainment in the gravity current as compared to the wall-jet is thereduction in the surface area of the isosurfaces.